2005
DOI: 10.1158/0008-5472.can-05-1036
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 and Claudin-4 Expression in Ovarian Epithelial Cells Enhances Invasion and Is Associated with Increased Matrix Metalloproteinase-2 Activity

Abstract: Claudin proteins form a large family of integral membrane proteins crucial for tight junction formation and function. Our previous studies have revealed that claudin-3 and claudin-4 proteins are highly overexpressed in ovarian cancer. To clarify the roles of claudins in ovarian tumorigenesis, we have generated human ovarian surface epithelial (HOSE) cells constitutively expressing wild-type claudin-3 and claudin-4. Expression of these claudins in HOSE cells increased cell invasion and motility as measured by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
331
1
11

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(362 citation statements)
references
References 43 publications
19
331
1
11
Order By: Relevance
“…Previous work has suggested that claudin-3 and claudin-4 overexpression in ovarian and other cancers may promote invasion and survival, but overexpression of claudins was not found correlated with barrier function [20]. Our current findings suggest that post-translation modifications of the overexpressed claudins may inhibit their TJ-related function while allowing other pro-oncogenic effects.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Previous work has suggested that claudin-3 and claudin-4 overexpression in ovarian and other cancers may promote invasion and survival, but overexpression of claudins was not found correlated with barrier function [20]. Our current findings suggest that post-translation modifications of the overexpressed claudins may inhibit their TJ-related function while allowing other pro-oncogenic effects.…”
Section: Discussioncontrasting
confidence: 48%
“…Mutant claudin-4 expression constructs were generated by PCR using the pCiNeo-CLDN4 expression plasmid previously described [20]. Point mutations of the serine or threonine residues in the consensus PKC site were introduced using the Quik-Change site-directed mutagenesis kit (Stratagene, La Jolla, CA).…”
Section: Expression Constructs Sirna and Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to an increased mRNA or protein stability. CLDN-3 and CLDN-4 are upregulated in ovarian and uterine cancers, 10,17,35,36 and CLDN-4 expression has been exploited for therapeutic purposes. 24 CLDN-7 expression is decreased in breast carcinomas, 13,37 but Adenocarcinoma vs bronchial cell (n ¼ 6) upregulated in gastric carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin-3 and claudin-4 are frequently expressed in OEC, as they aid in altering membrane permeability to facilitate invasion. Both of these proteins have been implicated in gelatinase activation [75,76].…”
Section: Mmps and Growth Factors In Matrix Remodelingmentioning
confidence: 99%